2018
DOI: 10.1002/cbf.3331
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐130b targets PTEN to induce resistance to cisplatin in lung cancer cells by activating Wnt/β‐catenin pathway

Abstract: More and more studies indicate the relevance of miRNAs in inducing certain drug resistance. Our study aimed to investigate whether microRNA‐130b‐3p (miR‐130b) mediates the chemoresistance as well as proliferation of lung cancer (LC) cells. MTS assay and apoptosis analysis were conducted to determine cell proliferation and apoptosis, respectively. Binding sites were identified using a luciferase reporter system, whereas mRNA and protein expression of target genes was determined by RT‐PCR and immunoblot, respect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
38
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 28 publications
0
38
0
1
Order By: Relevance
“… Furthermore, several studies suggest that miRNA‐mediated downregulation of PTEN might lead to new therapeutic strategies for NSCLC. In this study, using bioinformatics and luciferase assays, we first found that PTEN is a target gene of miR‐4286. Then, we examined the mRNA expression of PTEN in NSCLC tissues and normal lung tissues from 31 NSCLC patients and found that 21 NSCLC tissues (67.74%) had a high miR‐4286 level while presenting low PTEN mRNA expression (Figure C).…”
Section: Discussionmentioning
confidence: 99%
“… Furthermore, several studies suggest that miRNA‐mediated downregulation of PTEN might lead to new therapeutic strategies for NSCLC. In this study, using bioinformatics and luciferase assays, we first found that PTEN is a target gene of miR‐4286. Then, we examined the mRNA expression of PTEN in NSCLC tissues and normal lung tissues from 31 NSCLC patients and found that 21 NSCLC tissues (67.74%) had a high miR‐4286 level while presenting low PTEN mRNA expression (Figure C).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, we hypothesized that cisplatin resistance might be related to the aberrant expression of signaling molecules induced by DNA destruction, resulting in altered activation of associated pathways. Activation of the Wnt/β-catenin pathway leads to cisplatin resistance in lung cancer (13)(14)(15). Moreover, CK2 is a positive regulator of Wnt signaling (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, activation of the Wnt/β-catenin signaling pathway due to cytoplasmic glycogen synthase kinase-3β (GSK-3β) inhibition might explain cisplatin resistance observed in A549/cis-diamminedichloroplatinum (II) (DDP) cells (13). Furthermore, maternally expressed 3 and miR-130b were also shown to enhance cisplatin resistance by activating the Wnt/β-catenin signaling pathway in lung cancer (14,15). These findings suggest that Wnt/β-catenin signaling might be closely related to cisplatin resistance.…”
Section: Introductionmentioning
confidence: 99%
“…c-MYB, miR-21 and wnt signaling. We observed that the miRNAs affected by c-MYB transfections, as shown above, are involved in regulating wnt signaling 14,16,17,19 , and, moreover, one of the signaling pathway affected by miR-21 is wnt signaling pathway 14 , therefore, for our mechanistic studies on cisplatin resistance by c-MYB, through miR-21, we focused on wnt signaling pathway. We evaluated β-catenin phosphorylation through ELISA.…”
Section: C-myb and Cisplatin Resistance It Has Been Reported Previoumentioning
confidence: 98%
“…In order to understand the underpinning epigenetic effect of c-MYB on cisplatin resistance, we first looked at altered miRNA expression, particularly of those miRNAs that have been reported to have an impact on cisplatin resistance. The screened miRNAs with published reports on cisplatin sensitivity that were differentially expressed upon c-MYB over-expression were miR-21 14 , miR-27a 15 , miR-130b 16 , miR-137 17 , miR-200c 18 , miR-218 19 . We found that four miRNAs, miR-21, miR-27a, miR-130b and miR-218 were elevated in c-MYB overexpressing cells, whereas two miRNAs, miR-137 and miR-200c were expressed at reduced levels in c-MYB overexpressing cells ( Fig.…”
Section: C-myb and Cisplatin Resistance It Has Been Reported Previoumentioning
confidence: 99%